Research on Reservoir Emergency Dispatching under Sudden Water Pollution Incident——A Case Study of Hongshui River in the Upper Reaches of the Pearl River - BIAN Kaixuan; HUANG Qiang; YANG Yuanyuan; LIU Dengfeng; LIU Dong; HAN Zhiming; WAN Xin (Renmin Zhujiang)
The Pearl River is an important water source for Yunnan, Guizhou, Guangxi, Guangdong ,etc. It is extremely important to study the movement and diffusion process of water pollutants andthe countermeasures for sudden water pollution incident in this basin for water supply security.Assuming that an emergency event of substandard sewage discharging occurs approximately 12 kmdownstream of Longtan Reservoir (in Tian'e County, Guangxi) during the dry season, this paperformulates a reservoir emergency dispatching plan set, and simulates the movement process ofpollutants by the water quality model in the EIAW11 software package, and the concentration changeprocess of pollutants with different concentrations (taking BOD as an example)under differentdownstream sections and different river flows. The results show that the model can reasonablysimulate the movement process and impact range of pollutants, and the discharged flow of theLongtan reservoir that is required to achieve the up-to-standard pollutant concentration isobtained after analysis. The accurate dispatching for sudden water pollution incidents can berealized according to different up-to-standard positions, to minimize the consumption of waterresources and give full play to the role of Longtan reservoir. The simulation results couldprovide some scientific basis for the formulation of emergency plans for sudden water pollutionincidents in the Pearl River Basin.